(3TQM JPcQg GdWhSi aj GdgjFIs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s
(3ChdgG (B:s
(3HYO agQS GdBHhGH hGdOjHGLg (B: (3aEf Yde GdgjFg eQbGg efUhHg Edi eYGQL GdSehGJ GdYdi heOGQc eG ChOYgG Gddg ajgG ef HOGFY Mce dGjNU s
(3BNQgG (B:s
(3hCeG HYO eMOH Gdadc GdBYXe edGjYedg EdG Gddg SHMGfg s
(3Cda SfI (B811(3g` Hg agQS ddCHhGHs
(3Gdajde ZjQ ehLhOs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdadcs